Addressing Adolescent Substance Use: Teaching Screening, Brief Intervention, and Referral to Treatment (Sbirt) and Motivational Interviewing (Mi) to Residents. Issue 3 (July 2015) - Whittle, Amy E.; Buckelew, Sara M.; Satterfield, Jason M.; Lum, Paula J.; O'Sullivan, Patricia
Background: The American Academy of Pediatrics Committee on Substance Use recommends screening, brief intervention, and referral to treatment (SBIRT) at every adolescent preventive and all appropriate urgent visits. We designed an SBIRT curriculum as part of the adolescent block of a pediatric residency that combined online modules with an in-person workshop, faculty feedback on resident interactions with patients, and resident self-reflection on their motivational interviewing (MI) skills. Methods: To evaluate the curriculum, we measured resident satisfaction and self-reported confidence in using SBIRT and MI with teens using a retrospective pre/post questionnaire. We used qualitative analysis to evaluate the written comments from faculty observations of patient-trainee interactions and comments from resident self-reflection(s) on patient interactions. Results: Thirty-two residents completed the curriculum. Residents reported high satisfaction with the training. Comparing retrospective pre/post scores on the survey of resident self-reported confidence, measures increased significantly in all domains, including for both alcohol and other drug use. Regarding self-reported MI, skillfulness also increased significantly. Analysis of specific faculty feedback to residents revealed subthemes such as normalizing confidentiality and focusing more on the patient's perspectives on substance use. Resident reflections on their own abilities with SBIRT/MI focused on using the ruler tool and on adapting the MI style of shared decision-making. Conclusions: A curriculum that combines online training, small-group practice, clinical observations, and self-reflection is valued by residents and can increase resident self-reported confidence in using SBIRT and MI in adolescent encounters. Future studies should examine to what extent confidence predicts performance using standardized measures of MI skillfulness in patient encounters.